Answer:
Option (4)
Explanation:
cos(a + b) = cos(a)cos(b) - sin(a)sin(b) [Identity]
Since, sin(a) =
for a in quadrant II
Therefore, cos(a) =
![\sqrt{1-\text{sin}^2(a)}=\sqrt{1-((2)/(5))^2}](https://img.qammunity.org/2021/formulas/mathematics/college/t5j4mb8j3e92x75nhpc3gc36j9fvzhx2b3.png)
cos(a) =
But cosine of a is negative quadrant II
Therefore, cos(a) = -
![(√(21))/(5)](https://img.qammunity.org/2021/formulas/mathematics/college/8pbrc5nq4kwsbgz2cbmp999nczz54ed8mw.png)
And cos(b) =
for b in quadrant IV
Therefore, sin(b) =
![\sqrt{1-\text{cos}^(2)b}](https://img.qammunity.org/2021/formulas/mathematics/college/wnbrkwtq79dsfjw1it51p0w2yahftefawy.png)
=
![\sqrt{1-((1)/(3))^2}](https://img.qammunity.org/2021/formulas/mathematics/college/p2y0p0ye1rt3rbt3g3v2m0r83vmixbzuh8.png)
=
![(2√(2))/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ixkr5ej663s3hevd8vtpa4p2f5do4oc8jy.png)
But sine of an angle is negative in quadrant IV,
Therefore, sin(b) =
![-(2√(2))/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/n4au43vn7qxhajp8sdk1rvveubg4veohzh.png)
Now substituting these values in the identity,
cos(a + b) =
![(-(√(21))/(5))((1)/(3))-((2)/(5))(-(2√(2))/(3))](https://img.qammunity.org/2021/formulas/mathematics/college/tzc8cervg4sk0rtxrpsn1l5f0f4w3ers73.png)
=
![-(√(21))/(15)+(4√(2))/(15)](https://img.qammunity.org/2021/formulas/mathematics/college/8zczvzfcg7snx87osjfcer30sdjpouiv5k.png)
=
![(4√(2)-√(21))/(15)](https://img.qammunity.org/2021/formulas/mathematics/college/fdapsxy83fgdnm8vliyz54gjpiaqvkyzkw.png)
Therefore, Option (4) will be the answer.